The Learn Together programme (part B): evaluating co-designed guidance to support patient and family involvement in patient safety incident investigations - Ramsey, Lauren; Waring, Justin; Sheard, Laura; Halligan, Daisy; McHugh, Siobhan; Simms-Ellis, Ruth; Langley, Joe; Murray, Jenni; Rogerson, Olivia; O'Hara, Jane K. (Frontiers in Health Services, 2025)
BackgroundExpectations of patient and family involvement in investigations of healthcare harm are becoming conventional. Nonetheless, how people should be involved, is less clear. Therefore, the “Learn Together” guidance was co-designed, aiming to provide practical and emotional support to investigators, patients and families.AimTo longitudinally evaluate use of the Learn Together guidance in practice—designed to support patient and family involvement in investigations of healthcare harm.MethodsA 15-month process evaluation took place across five sites, following 29 investigations in which the Learn Together guidance was used. Sites comprised two mental health and two physical health hospital Trusts, and an independent maternity investigatory body in England. Longitudinally, 127 interviews were conducted with investigators, patients, families, staff, and management. Interview and observational data were synthesized using Pen Portraits and analyzed using multi-case thematic analysis.FindingsThe guidance supported the systematic involvement of patients and families in investigations of healthcare harm and informed them how, why, and when to be involved across settings. However, within hospital Trusts, investigators often had to conduct “pre-investigations” to source appropriate details of people to contact, juggle ethical dilemmas of involving vs. re-traumatizing, and work within contexts of unclear organizational processes and responsibilities. These issues were largely circumvented when investigations were conducted by an independent body, due to better established processes, infrastructure and resources, however independence did introduce challenge to the rebuilding of relationships between families and the hospital Trust. Across settings, the involvement of patients and families fluctuated over time and sharing a draft investigation report marked an important part of the process—perhaps symbolic of organizational ethos surrounding involvement. This was made particularly difficult within hospital Trusts, as investigators often had to navigate systemic barriers alone. Organizational learning was also a challenge across settings.ConclusionsInvestigations of healthcare harm are complex, relational processes that have the potential to either repair, or compound harm. The Learn Together guidance helped to support patient and family involvement and the evaluation led to further revisions, to better inform and support patients, families and investigators in ways that meet their needs (https://learn-together.org.uk). In particular, the five-stage process is designed to center the needs of patients and families to be heard, and their experiences dignified, before moving to address organizational needs for learning and improvement. However, as a healthcare system, we call for more formal recognition, support and training for the complex challenges investigators face—beyond clinical skills, as well as the appropriate and flexible infrastructure to enable a receptive organizational culture and context for meaningful patient and family involvement.